Vermont State Colleges. Futures Task Force II Report - Vermont State Commission on Higher Education; Vermont State Commission on Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
This report presents recommendations to strengthen quality and improve programs and services in the Vermont State College (VSC) for Vermont and Vermonters for the next 10-15 years. The report notes three major changes in the VSC and in the role which education beyond high school plays: that VSC enrollments have increased by 37 percent in the past 6 years; that the gap between the earning power of high school and college graduates has widened greatly in recent years; and that there has been a worsening financial crisis developing over the years for both the students and VSC. Recommendations proposed include the following: (1) reaffirm VSC's public mission, i.e., its purposes and expectations for investment in higher education, as its cornerstone; (2) modestly expand the VSC's library, academic, and student housing capacity; (3) strengthen the five VSC's identities and individual characters as learning communities; (4) forge new relationships with K-12 educational institutions in Vermont; (5) further expand VSC's direct contributions to economic development in Vermont; and (6) help create a financial future which will assure Vermonters access to affordable, high quality public higher education. Appendices present trends in high school graduates during 1977-2000, data on educational attainment and personal income, and data on student family income and loan burdens. Contains 21 references. (GLR)
Administrators.
Policymakers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Educational Facilities; Educational Planning; Educational Quality; Enrollment; Expenditures; Financial Exigency; Financial Problems; Futures (of Society); Higher Education; Income; Institutional Mission; Long Range Planning; State Schools; Trend Analysis; Vermont State Colleges; Opinion Papers